CORPORATE SOCIAL RESPONSIBILITY - Defril, Defril Hidayat (Fakultas Hukum, Universitas Samudra, 2023)
This research will focus on CSR which is the obligation of the company to be responsible in terms of development and social around the company, where each company must provide CSR funds from the company's profits to help the development around the company operates, this is expected to be a solution to the problem of social and environmental development, in some developed countries CSR takes a broader role by reaching out to partners for regional infrastructure development, this has not been touched in the rules of legislation in Indonesia, therefore it is very interesting to study more deeply the opportunities and future layout. The purpose of this study is to look at the possibilities and analyze the opportunities and challenges that need to be resolved to make CSR actively involved in regional infrastructure development. This research method is normative juridical, where it is done by analyzing the relevant legal rules in order to understand the subject matter in the rules of the game so that a solution can be found to the problem at hand .From the analysis conducted, it can be concluded that CSR has been running as mandated by the law, but those aspects to be able to make CSR a development partner still have empty space that must be regulated with certainty and measured by the rules of the law.